Physician-defined severe toxicities occurring during and after cancer treatment: Modified consensus definitions and clinical applicability in the evaluation of cancer treatment - Nielsen, Camilla Grud; Thomsen, Birthe Lykke; Als-Nielsen, Bodil; Conyers, Rachel; Jeha, Sima; Mateos, Marion K.; Mlynarski, Wojciech; Pieters, Rob; Rathe, Mathias; Schmiegelow, Kjeld; Andrés-Jensen, Liv (Frontiers in Pediatrics, 2023)
Overall survival after cancer is increasing for the majority of cancer types, but survivors can be burdened lifelong by treatment-related severe toxicities. Integration of long-term toxicities in treatment evaluation is not least important for children and young adults with cancers with high survival probability. We present modified consensus definitions of 21 previously published physician-defined Severe Toxicities (STs), each reflecting the most serious long-term treatment-related toxicities and representing an unacceptable price for cure. Applying the Severe Toxicity (ST) concept to real-world data required careful adjustments of the original consensus definitions, translating them into standardized endpoints for evaluating treatment-related outcomes to ensure that 1) the STs can be classified uniformly and prospectively across different cohorts, and 2) the ST definitions allow for valid statistical analyses. The current paper presents the resulting modified consensus definitions of the 21 STs proposed to be included in outcome reporting of cancer treatment.